Fruit and vegetable intake is associated with frequency of breakfast, lunch and evening meal: cross-sectional study of 11-, 13-, and 15-year-olds - Pedersen Trine; Meilstrup Charlotte; Holstein Bjørn E; Rasmussen Mette (BMC, 2012)
Abstract Background Frequency of eating breakfast, lunch and evening meal as a determinant of fruit and vegetable intake among young people is little studied. We investigated whether irregular meal consumption was associated with fruit and vegetable intake among adolescents. We used separate analyses, and special emphasis was on the potentially modifying effect of sex and age. Methods Data were from the Danish contribution to the international collaborative Health Behavior in School-Aged Children Study (HBSC) in 2002. We used a questionnaire-based, cross-sectional design to study schoolchildren aged 11, 13 and 15 years (n = 3913) selected from a random sample of schools in Denmark. Fruit intake and vegetable intake were measured by a food frequency questionnaire and analyses were conducted using multivariate logistic regression. Results Overall, statistically significant associations were found between irregular breakfast, lunch and evening meal consumption and low frequency of fruit intake and vegetable intake (breakfast: fruit OR = 1.42, vegetables OR = 1.48; lunch: fruit OR = 1.68, vegetables OR = 1.83; evening meal: vegetables OR = 1.70). No association was found for irregular evening meal consumption and low frequency of fruit intake. Analyses stratified by sex showed that the associations between irregular breakfast consumption and both fruit and vegetable intake remained statistically significant only among girls. When analyses were stratified by both sex and age, different patterns appeared. Overall, skipping meals seemed to be a less serious risk factor for low frequency of fruit and vegetable intake among younger participants compared with those who were older. This was especially evident for skipping breakfast. The same tendency was also seen for skipping lunch and evening meal, although the age pattern varied between boys and girls and between fruit and vegetable intake. Conclusion Our results showed that irregular breakfast, lunch and evening meal consumption among adolescents was associated with a low frequency of fruit and vegetable intake and that sex and age may play a modifying role. The different associations observed in different age and sex groups indicate the importance of analysing fruit and vegetable intake and meal types separately. The results highlight the importance of promoting regular meal consumption when trying to increase the intake of fruit and vegetables among adolescents.